(untitled) (Research, Society and Development, 2023)
Rivers are sources of natural resources and indispensable to life, in addition to having great cultural, economic and historical importance for the cities where they are located, but due to some human actions they end up being harmed. Given this, this article aims to verify the bathing conditions of four sampling points on the Grajaú River, in the city of Grajaú-Ma, where the pH measurement and microbiological tests for the detection of Escherichia coli (E. coli), Enterobacter cloacae (E. cloacae) and total coliforms, in the following points: Prainha (I), Canecão (II), Sirigueijo (III) and Limoeiro (IV), classifying the waters in relation to bathing as: excellent, very good, satisfactory and inappropriate. The methodology used offers a precise and comprehensive way to assess water quality with microbiological analysis, through the potability kit with mini greenhouse and colipaper, involving qualitative and quantitative methods. The results show that the points closest to the spring, where they receive little waste, are of better quality, while the points below where bathers frequent, are points with greater risks of microbiological contamination, with lower water quality. It was concluded that based on the results, certain areas are not suitable for bathing because they indicate the presence of fecal and total coliforms. Thus, it is important to emphasize that the presence of these coliforms suggests the possible existence of other pathogenic microorganisms in the water, capable of causing gastrointestinal disorders and infections in humans. It is therefore crucial to take steps to ensure water safety and protect public health.